Dari Wahyu ke Tradisi: Makkalepu dan Epistemologi Pembacaan Al-Qur’an dalam Kebudayaan Sulawesi Selatan - Kamaruddin Mustamin; Muhammad Alwi HS (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This article aims to explore makkalepu as a representation of Qur’anic reading epistemology within the cultural context of South Sulawesi, functioning as a medium for transmitting divine revelation through traditional praxis. The author argues that makkalepu is not merely a method for learning Arabic script (huruf hijaiyyah), but a form of lived knowledge embedded in the cultural space of Muslim communities. This study employs a qualitative approach using ethnographic methods. Data were collected from both fieldwork and textual sources, then analyzed through the lens of local epistemology. The article finds that makkalepu serves as a pedagogical method for Qur’anic instruction that contains a localized epistemological system in the process of transforming revelation into a lived Islamic tradition. As a form of living epistemology, makkalepu reflects the integration of Islamic values with the cultural fabric of South Sulawesi. Its presence affirms that Islamic epistemology is not ahistorical or purely ideal, but capable of evolving within rooted and dynamic cultural contexts. These findings are significant for the development of contemporary Islamic epistemology, particularly in highlighting how revelation is understood, experienced, and transmitted through localized and practical traditions.